Instantaneous achievement of the hall and Pedersen-Cowling current circuits in northern and southern hemispheres during the geomagnetic sudden commencement on 12 May 2021 - Kikuchi, Takashi; Araki, Tohru; Hashimoto, Kumiko K.; Ebihara, Yusuke; Tanaka, Takashi; Nishimura, Yukitoshi; Vichare, Geeta; Sinha, Ashwini K.; Chum, Jaroslav; Hosokawa, Keisuke; Tomizawa, Ichiro; Tanaka, Yoshimasa; et al. (My University, 2022)
The present article aims at a consistent understanding of observation, theoretical model, and simulation with the geomagnetic sudden commencement (SC) observed in the morning and afternoon at high and middle latitudes in the northern and southern hemispheres and at the noontime equator on 12 May 2021. The SC in Bx- and By-components of the geomagnetic field, SCx,y, was composed of the positive/negative preliminary (PI) and main impulses (MI) as SCx (+ -) and SCy (- +) in the morning and SCx (- +) and SCy (+ -) in the afternoon at middle latitudes in the northern hemisphere. SCx in the southern hemisphere is in the same polarity as those in the northern hemisphere, except for SCx (+ +) in the morning. SCy in the southern hemisphere has reverse polarity to those in the northern hemisphere. The PIx in the northern hemisphere matches the well-established two-cell Hall current vortices with anti-clockwise and clockwise directions in the morning and afternoon, respectively, and the MIx matches reverse Hall current vortices. The PIx and MIx in the southern hemisphere meet the Hall currents that are mirror images of those in the northern hemisphere with respect to the equator except for the positive MI in the morning. The PIy in the northern hemisphere is shown to meet the northward and southward Pedersen currents in the morning and afternoon, respectively, and the MIy meets reverse Pedersen currents. The PIy and MIy in the southern hemisphere are found to meet the Pedersen currents that are mirror images of those in the northern hemisphere. At the equator, typical SCx (- +) is observed, meeting the Cowling currents that should be supplied by the Pedersen currents responsible for the observed midlatitude SCy in the northern and southern hemispheres. The electric fields of the PI and MI observed by the HF Doppler sounders at the middle latitudes in the northern hemisphere are westward and eastward, respectively, in both the morning and afternoon, meeting the conventional dusk-to-dawn PI and dawn-to-dusk MI electric fields. The onset of the PI is found to be simultaneous with the resolution of a few seconds from high latitude to the equator in both the northern and southern hemispheres, indicating instantaneous achievement of the Pedersen–Cowling currents from high latitude to the equator. The instantaneous achievement of the energy-consuming Pedersen–Cowling currents is explained by the TM0/TEM mode wave in the Earth-ionosphere waveguide/transmission line rather than the compressional waves in the magnetosphere and F-region ionosphere. REPPU (REProduce Plasma Universe) global simulation model equipped with a potential solver at the inner boundary of the model magnetosphere reproduces the PI and MI electric fields at middle latitudes and SCx (- +) at the dayside equator. The simulation results are found to be consistent with most features of observations, such as the time scale of PI and MI, direction of the midlatitude electric field and generation of the Cowling currents. The simulation proves that the electric fields and FACs are generated in the outer magnetosphere, transmitted to the polar ionosphere and then to the equator in the Pedersen–Cowling current circuit.
Keywords: Geomagnetic sudden commencement; Hall current circuit; Pedersen-Cowling current circuit; Simultaneous onset of preliminary impulse; Morning afternoon symmetry asymmetry; Northern and southern hemispheric symmetry/asymmetry; HF Doppler sounder; Global simulation